PENGARUH MANAJEMEN LABA DAN RASIO KEUANGAN PERUSAHAAN TERHADAP NILAI PERINGKAT OBLIGASI - Novela Sari, Elivia; Hidayati, Siti Aisyah (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2024)
This research aims to analyze the influence of earnings management and financial ratios on bond rating values (Study of companies listed on the Indonesian Stock Exchange for the 2022 period). This type of research is associative research. The population in this study were 44 financial companies that issued bonds. Sampling in this study used a purposive sampling method with certain criteria, namely 44 bond issuing companies. The research variables in this study use Earnings Management proxied by Estimated Management Accruals (EDAit) and Solvency Ratio proxied by Debt to Equity Ratio (DER) and Activity Ratio proxied by Total Asset Turnover (TAT) as an independent variable, and Bond Rating Value as a variable dependent. The analysis method in this research uses Logistic Regression analysis techniques. The results of this research show that Earnings Management (EDAit) has no effect on the Bond Rating Value, the Solvency Ratio (DER) has a positive and significant effect on the Bond Rating Value, and the Activity Ratio (TAT) has no effect on the Bond Rating Value.